الاكتئاب وعلاقته بمرض السكري عند المسنين "دراسة ميدانية على عينة من المسنين المقيمين في دار السعادة والكرامة بمدينة دمشق" - نعامة سليم; العريضي صفاء عبدالله (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يُعَدُّ الاكتئاب من أكثر الاضطرابات النفسية الشائعة بين المسنين وخصوصاً ذوي الأمراض الجسمية المزمنة وبشكل خاص مرضى السكري, فلذلك تحددت مشكلة البحث بالسؤال التالي: ما هي العلاقة بين مرض السكر والاكتئاب عند المسنين؟ ولقد تناولت عينة البحث المسنين المقيمين في دار السعادة والكرامة في مدينة دمشق وبلغت عينة البحث 40 مسناً ومسنة وتكونت العينة من40 مفحوصاً من الأفراد المسنين فوق الـ60 سنة و استخدمت الباحثة في دراستها الحالية مقياس الاكتئاب للمسنينD.E.S والذي يحتوي على 80 عبارة وذلك لقياس الاكتئاب لدى المسنين. ولقد كشفت الدراسة عن: أنه بوجود مرض السكر عند المسن ترتفع لديه احتمالية الإصابة بالاكتئاب أو بزيادة أعراضه مقارنة مع غير المصابين بمرض السكري, والعكس صحيح وأن الإناث سجلت درجات مرتفعة على مقياس الاكتئاب مقارنة مع الذكور وأنه كلما كان التحصيل التعليمي متدنياً زاد من نسبة الاكتئاب عند المسنين المصابين بمرض السكري. Depression is considered to be one of the most common mental disorders among the elderly, especially among those with chronic physical diseases in particular Diabetes. Therefore research problem was defined by the following question: What is the relationship between diabetes and depression in the elderly?, and have dealt with the research sample "elderly" residents in Dar Al-saadah and Al-karamah in Damascus. Research sample has reached the number of 40 of the elderly and consisted of 40 examined individuals aged over 60 years old. The researcher used the Depression Scale for the Elderly D.E.S in her current study which contains 80 phrases to measure the level of depression in the elderly. The study has revealed that the potential incidence with depression and the intensity of its symptoms increase when an elderly is diabetic compared with non-diabetic and vice versa, it also revealed that females have recorded higher levels of depression on the depression scale compared with males, it also showed that whenever there is a lower educational level among diabetics elderly the rate of the incidence with depression increases.